Assessment of the hygiene conditions of domestic lunch boxes produced in Itapetinga – BA: Hygiene knowledge of food handlers (Research, Society and Development, 2023)
Food handlers play an important role in the hygienic and sanitary control of food, so it is important that there is greater care on the part of them in relation to food production. In food services, food handlers are one of the most important foundations for a safe environment and for food handling to take place with greater safety and quality. The objective was to evaluate the hygiene knowledge of lunchbox food handlers in the city of Itapetinga, BA. The research was carried out with 5 establishments that offered domestic lunchboxes and a total of 10 food handlers. To assess the conditions under which lunchboxes are being produced, a questionnaire was applied to food handlers, based on the World Health Organization booklet and RDC 216/2004, which provides for the technical regulation of Good Practices for food services. The questionnaire lasted 10 to 15 minutes. In this study, it was possible to identify the hygiene knowledge of food handlers in relation to practical day-to-day issues within the processing of domestic lunchboxes, showing that although they have knowledge, it is still important that they are trained in this regard. Knowing this profile is essential for public policy planning and training in good manufacturing practices. The results showed that food handlers still have some practices considered erroneous by current legislation, which may lead to contamination of lunchboxes that are being produced.